CAN THERE BE HAPPINESS IN PSYCHOANALYSIS? CREON AND ANTIGONE IN LACAN´S SEMINAR VII - Balaska, Maria (Johns Hopkins University, 2018)
This essay shows that despite the psychoanalytic critique of the human search for happiness as futile and illusory, there can still be a positive contribution to the question of happiness from psychoanalysis. To that end, the paper turns to Lacan’s Seminar VII, and more specifically, to the Lacanian “sublimation” as “the happy satisfaction of the instinct.” Whether we can achieve a non-illusory kind of happiness through sublimation or we stay trapped in the pursuit of an illusory happiness depends on the extent to which we succeed or fail in the following two issues: 1. asking whether we have ceded on our desire and 2. accepting that no object of desire can ever be completely satisfying. Lacan offers two examples of a problematic relation to desire: these of Creon and Antigone; Creon fails to ask the question about his desire altogether, while Antigone asks the question but fails to accept that she cannot have it all. A critical reflection of these two cases can allow us to find a positive and sustainable version of happiness in psychoanalysis.
CAN THERE BE HAPPINESS IN PSYCHOANALYSIS? CREON AND ANTIGONE IN LACAN´S SEMINAR VII
Keywords: Feminism; Happiness; Ethics; Psychoanalysis; Civilization; Feminism; Happiness; Ethics; Psychoanalysis; Civilization